Analisis Teori Eskalasi Glasl pada Konflik Palestina-Israel - Hamidah, Virda Meilani; Hakiem, Fadhlan Nur (Peneliti.net, 2024)
The Palestinian-israel conflict has lasted a long time, and is no longer a religious conflict like most would say, but is a humanitarian conflict because it has taken many lives. The study USES the glasl escalation theory of analysis. Based on the results of the foregoing discussion, a analysis of the glasl escalation of the palestina-israel conflict divides chronology ata high level by the first, second, and third levels. In the first stage the conflict is still declaimed debate and talks, with the formation of the Zionism movement and the Balfour declaration, and then followed by the second level of covering the establishment of the state of Israel. Then it continues with the third stage in which conflict begins a deadly struggle, such as in the six-day war until the hamas attacks in 2023. It is hoped that this analysis and discussion will provide knowledge of the root of the Palestinian conflict and that it can provide solutions to resolve it.